Historicising global nutrition: Critical reflections on contested pasts and reimagined futures - Nelson, Erika Marie; Nisbett, Nicholas; Gillespie, Stuart (BMJ, 2021)
The COVID-19 pandemic has provoked a range of economic shocks, food systems shocks, public health crises and political upheavals across the globe, prompting a rethink of associated global systems. Prepandemic anticolonial movements that challenged hierarchies of race, space, gender and expert knowledge in global health took on new meaning in the context of the unequal impacts of the SARS-CoV-2 virus as it moved through different kinds of spaces and distinct political contexts. In light of these dynamics, and the desire of many current practitioners in global health to reimagine the future, the need for critical analyses of the recent past have become more urgent. Here we challenge linear understandings of progress in global health—with a focus on the field of nutrition—by returning to consider a previous cycle of dramatic social, political and economic change that prompted serious challenges to the dominance of Western powers and US-based philanthro-capitalists. With a ‘global’ health and nutrition audience in mind, we put forward considerations on why a better understanding of the continuities and divergences between this past and the present moment are necessary to challenge a status quo that was, and is, highly flawed.